The magic of internet protocol - Batiha, Khaldoun (Journal of Advanced Computer Science & Technology, 2017)
As the developing use of web and intranet keep on expanding colossally, the issue to suit more clients and gadgets has been risen. Subsequently, a location range must be required to oblige the hurry. Sadly, IPv4 address region and alternatives are insufficient to meet this new necessity. A fresh out of the box new Protocol is expected to satisfy the developing interest. IPv6 is the best response to the above issues. We should have an early on study on IPv6 convention. IPv6 convention offers verity of advantages that incorporates a more extensive location region and upgraded choices and changes that are not beforehand be found in the IPv4. IPv6 in contrast with IPv4 have a wide address range, simple documentations for representation of a location, enhanced administrations and alternatives, upgraded header, propelled highlights, new choices and bolster, auto setup highlight, new convention bolster, Network Security, Virus and Worms Security, Support for different Operating frameworks and stage including Microsoft windows, Linux and MAC.